Arabic Key Consonants - bar-Lev, Zev (Journal of Arabic and Islamic Studies, 2017)
This article outlines an approach to lexicon in Arabic linguistics, with special implications for teaching Arabic as a foreign language. Its basic insight is that individual initial consonants have their own meanings. On a theoretical level, this key-consonant system offers a pervasive theoretical insight about the structure of a lexicon, and the nature of lexical acquisition; and on a practical level, it offers a powerful key to learning vocabulary in L2—which in turn may offer the best possible validation of the theoretical claim. It is here related to insights in linguistic theory on the submorpheme (and analogical modeling); in L2 learning, such submorphemes can help make learning of vocabulary easier, and sometimes even make it possible to guess the meanings of new roots in context. An additional implication for the history of Semitic linguistics is also drawn, proposing to bring back into Semitic linguistics a set of insights that had been “banished” from the mainstream with the advent of “scientific” Semitic grammar over a thousand years ago. On the other hand, we will draw a sharp distinction between the proposal and biconsonantal root theory, with which it might be confused on first impression.